Intravenous Dexmedetomidine Provides Superior Patient Comfort and Tolerance Compared to Intravenous Midazolam in Patients Undergoing Flexible Bronchoscopy. (12th October 2015) - Goneppanavar, Umesh; Magazine, Rahul; Periyadka Janardhana, Bhavya; Krishna Achar, Shreepathi
Abstract : Dexmedetomidine, an α 2 agonist, has demonstrated its effectiveness as a sedative during awake intubation, but its utility in fiberoptic bronchoscopy (FOB) is not clear. We evaluated the effects of midazolam and dexmedetomidine on patient's response to FOB. The patients received either midazolam, 0.02 mg/kg (group M, n = 27 ), or dexmedetomidine, 1 µ g/kg (group D, n = 27 ). A composite score of five different parameters and a numerical rating scale (NRS) for pain intensity and distress were used to assess patient response during FOB. Patients rated the quality of sedation and level of discomfort 24 h after the procedure. Ease of bronchoscopy, rescue medication requirement, and haemodynamic variables were noted. Ideal or acceptable composite score was observed in 15 and 26 patients, respectively, in group M (14.48 ± 3.65) and group D (9.41 ± 3.13), p < 0.001 . NRS showed that 11 patients in group M had severe pain and discomfort as compared to one patient with severe pain and two with severe discomfort in group D during the procedure, p < 0.001 . Rescue midazolam requirement was significantly higher in group M (p = 0.023 ). We conclude that during FOB, under topical airway anaesthesia, IV dexmedetomidine (1 µ g/kg) provides superior patient comfort and tolerance as compared to IV midazolam (0.02 mg/kg).